Checkbook Zionism : philanthropy and power in the Israel-Diaspora relationship - Fleisch, Eric, 1975- (Rutgers University Press, 2024)
American Jews donate approximately $2.5 billion to Israel each year. Behind all that money and influence lies a power-sharing dynamic that has left an indelible mark on the relationship between Israeli and American Jews and on the direction of Israeli society to this day. Checkbook Zionism investigates how both parties have managed their interests, emotions, and attitudes about the important yet at times tense collaboration between them. By delving into the history of American Jews'philanthropic giving to Israelis, Fleisch assesses the core nature of power sharing between both sides of the Jewish diaspora to the United States through in-depth contemporary case studies of the relationship between sixteen non-governmental organizations and their American Jewish donors. Field observation, document analysis, and interviews with leaders, activists, and select donors alike serve a critical role here, as Fleisch assesses whether these contemporary philanthropic associations repeat classic dynamics of power-sharing or whether they represent a marked departure from the Checkbook Zionism of old. The result is a new paradigm for evaluating power sharing that can be applied to future considerations of development in the Israel-Diaspora relationship.